A survey of the school libraries and audiovisual centers administered by the Missionary Sisters of the Immaculate Conception with implications for development planning - Gumnad, Ma. Socorro G. (1987)
The survey of the school libraries and audiovisual centers administered by the Missionary Sisters of the Immaculate Conception (MIC) aimed to gather salient information about the present condition of these institutions. The survey intended to find out the extent of development of the library and audiovisual centers by looking into the: 1) statement of objectives; 2) library personnel; 3) budget and sources of financial support; 4) the collection; 5) organization of the collection; 6) library/audiovisual programs and services; and the 7) equipment, facilities and quarters. The findings are meant to serve as bases for recommending improvements, if necessary, in these libraries and audiovisual centers.